Arteriovenous Fistula Salvage Utilizing a Hybrid Vascular Graft. Issue 2 (March 2014) - Jones, Robert G.; Inston, Nicholas G.; Brown, Timothy
Introduction: Loss of arteriovenous fistula as access for hemodialysis leads to significant morbidity and increased mortality risk. Methods: Maintenance of this access is of paramount importance and we describe a case of a patient with a functioning radiocephalic fistula with associated arm swelling due to poor narrow caliber venous drainage above the elbow but with normal central veins. Results: A hybrid vascular graft was anastomosed to the upper extent of the fistula and the nitonol stent section introduced into the patent axillary vein. Conclusion: The described method led to resolution of symptoms and arm swelling. The described method allowed the continued use of a mature fistula.